Adapting a medication adherence app for adolescents and young adults in Makurdi, Benue State: The Lu Dedoo Project - Olaposi Joseph Olatoregun; Lisa Hightow-Weidman; Marta Mulawa; Lauren Jennings; Jay Osi Samuels; Prosper Okonkwo; Catherine Orrell (PLoS ONE, 2026)
Introduction Adolescents and young adults living with HIV (AYALHIV) face persistent challenges with antiretroviral therapy (ART) adherence, a key determinant of viral suppression and long-term health outcomes. The Lu Dedoo Project sought to adapt the existing (Masakhane Siphucule Impilo Yethu (MASI) adherence app, originally developed for South Africa, for AYALHIV in Benue State, Nigeria. Guided by a human-centered design (HCD) framework, the project engaged end users to ensure that the app was contextually relevant, user-friendly, and responsive to local needs prior to pilot testing. Methods Beta testing was conducted where purposively selected AYALHIV used MASI in its existing form for one month. Three subsequent FGDs were held among beta testers, involving a total of 22 participants: one mixed-gender adolescent group aged 15–19 years (n = 6), one male young adult group aged 20–24 years (n = 8), and one female young adult group aged 20–24 years (n = 8). FGDs were analysed using thematic analysis in NVivo® v15. Transcripts were analysed thematically to identify user experiences and desired modifications. Identified features were then prioritised using the MoSCoW method (“Must have,” “Should have,” “Could have,” “Won’t have”) to guide development decisions and ensure feasible, user-driven adaptation. Results Participants found the app highly engaging and liked the games, quizzes, and the ability to earn badges. These features contributed to user retention and supported their medication adherence. A subset of participants noted the challenge of needing cellular data access to use the app. “Must have” priorities included offline access to key features, simplified navigation, and customizable medication reminders. “Should have” and “Could have” priorities included adding more engaging media content and enhancing personalised reminders to better meet user needs. Conclusions Applying an HCD framework, complemented by MoSCoW prioritisation, provided a structured and participatory pathway for adapting an mHealth adherence app to the Nigerian context. The process ensured that core user needs guided technical decisions and that limited development resources were directed toward high-impact features. The adapted Lu Dedoo app reflects local preferences for functionality, language, and offline usability, and represents a promising, context-specific tool for improving ART adherence among AYALHIV.